Effects of pain on depression, sleep, exercise tolerance, and quality of life in patients with nontuberculous mycobacterial pulmonary disease. Issue 23 (11th June 2021) - Mori, Kosuke; Tabusadani, Mitsuru; Yamane, Kazumasa; Takao, Satoshi; Kuroyama, Yuki; Matsumura, Yusuke; Ono, Kazuki; Kawahara, Kazuma; Omatsu, Shunya; Fujiwara, Keiji; Furuuchi, Koji; Morimoto, Kozo; et al.
Abstract : Abstract: The experience and causes of pain in patients with nontuberculous mycobacterial pulmonary disease (NTM-PD) have not been clarified. This study aimed to determine the prevalence and severity of bodily pain (BP) in patients with NTM-PD. We also investigated the clinical indicators that contribute to pain. We used a retrospective cross-sectional study design. The participants were 114 NTM-PD patients (109 women) with a mean age of 65 years. The prevalence and severity of pain were measured using 2 items from the 36-Item Short Form Survey version 2 (SF-36), and the BP score was calculated. Functional limitation due to dyspnea was quantified using the Modified Medical Research Council Dyspnea Scale (mMRC), depression was assessed using the Center for Epidemiological Studies Depression Scale (CES-D), sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI); health-related quality of life was assessed using the Leicester Cough Questionnaire (LCQ), and exercise tolerance was measured using the Incremental Shuttle Walk Test (ISWT). Pain was reported by 70.2% of the patients (n = 80), and of these, 35.7% (n = 25) reported moderate to very severe pain. NTM-PD patients with high levels of pain had significantly higher scores on the mMRC, CES-D, and PSQI scores, and significantly lower performance on the ISWT and LCQ. Multiple regression analysis identified ISWT, CES-D, and PSQI as independent factors that affected BP scores. Our findings suggest that pain significantly impacts daily life associated with reduced exercise tolerance, the presence of depressive symptoms, and poor sleep quality in patients with NTM-PD.